Anti-Money-Laundering and Countering Financing of Terrorism Risk Management in Emerging Market Banks : Good Practice Note (International Finance Corporation, Washington, DC, 2019)
The International Finance Corporation (IFC) is the private sector arm of the World Bank Group (WBG) and one of the leading investors and lenders in emerging markets. Efforts to strengthen the global financial system following the 2007-2008 global financial crisis have contributed to withdrawal of correspondent banking services, which has a disproportionately negative impact on emerging markets. Increasingly, correspondent banks are paying greater attention to their respondents’ anti-money laundering and combating the financing of terrorism (AML and CFT) program effectiveness, know your customer and customer due diligence (KYC and CDD) programs, and their jurisdiction-related obligations to comply with AML and CFT requirements. In the survey, private sector emerging market banks identified assistance with understanding and adapting to new global standards as one solution component that will be most useful. In response, IFC has published this good practice note: AML and CFT risk management in emerging market banks (GPN) for banks to advance their knowledge and capabilities in AML and CFT risk management and facilitate and support the maintenance of correspondent banking relationships (CBRs).